Evolutionarily Selected Overexpression of the Cytokine BAFF Enhances Mucosal Immune Response Against P. falciparum - Lodde, Valeria; Floris, Matteo; Beerman, Isabel; Munk, Rachel; Guha, Rajan; Steri, Maristella; Orrù, Valeria; Abdelmohsen, Kotb; Crompton, Peter D.; Gorospe, Myriam; Idda, Maria Laura; Cucca, Francesco (Frontiers in Immunology, 2020)
We have previously shown that a variant of the TNFSF13B gene that we called BAFF-var, increases the production of the cytokine BAFF, up-regulating humoral immunity and increasing the risk for certain autoimmune diseases. In addition, genetic population signatures revealed that BAFF-var was evolutionarily advantageous, most likely by increasing resistance to malaria infection which is a prime candidate for selective pressure. To evaluate whether the increased soluble BAFF (sBAFF) production confers protection, we assessed experimentally the role of BAFF-var in response to malaria antigens. Lysates of erythrocytes infected with Plasmodium falciparum (iRBCs) or left uninfected (uRBCs, control) were used to treat PBMCs and B cells with distinct BAFF genotypes. The PBMCs purified from BAFF-var donors and treated with iRBCs showed different levels of specific cells, immunoglobulins and cytokines as compared with BAFF-WT. In particularly a relevant differential effect on mucosal immunity B subpopulations have been observed. These findings point to specific immune cells and molecules through which the evolutionary selected BAFF-var may have improved fitness during P. falciparum infection.